Analysis of influencing factors and nursing interventions of patients with mental abnormality after orthotopic liver transplantation - Yan, Jinghui; Wu, Li; Wang, Yingying; Ma, Ruisi; Shi, Yanmin; Chen, Yajie (Frontiers in Surgery, 2025)
ObjectiveTo analyze the influencing factors and nursing interventions of patients with mental abnormality after orthotopic liver transplantation.MethodsThe clinical data of one hundred patients received orthotopic liver transplantation in our hospital from January 2022 to June 2023 were selected to be study objects. Patients were divided into research group (40 cases) and control group (60 cases) according to whether psychiatric symptoms occurred after surgery. Correlation statistical analysis methods such as univariate Logistic regression and binary logistic regression were used to analyze the correlation between the general condition, preoperative, intraoperative and postoperative related indicators and the occurrence of postoperative neuropsychiatric complications in the two groups.ResultsThere were no deaths during perioperative period. Neuropsychiatric complications occurred in 40 of 100 cases. Univariate analysis results displayed that there were significant differences in preoperative hepatic encephalopathy and grade C liver function between 2 groups (P < 0.01), there was significant difference in the average amount of intraoperative blood loss between the two groups (P < 0.01), and there were significant differences in postoperative intensive care unit (ICU) treatment time, FK506 concentration, and electrolyte disturbance between 2 groups (P < 0.05 and P < 0.01). Binary Logistic regression analysis results showed that grade C liver function, postoperative ICU treatment time, FK506 concentration and electrolyte disturbance were risk factors for neuropsychiatric complications after liver transplantation (P < 0.01).ConclusionGrade C liver function, postoperative ICU treatment time, FK506 concentration, and electrolyte disturbance are risk factors for neuropsychiatric complications after liver transplantation. According to the above risk factors, standardized management and psychological counseling should be carried out.